Considerations for the physical preparation of freestyle snowboarding athletes - Dann, R. A.; Kelly, V. G. (Strength and Conditioning Journal, 2022)
The rapid growth in trick progression for competitive snowboarding over the past 20 years has resulted in increased physical demands required from snowboarding athletes. Despite a wealth of knowledge surrounding strength and conditioning principles for other sports, researchers are yet to address the novel strength and conditioning challenges faced by the freestyle nature of competitive snowboarding. This article, therefore, offers practitioners strategies to address the unique considerations surrounding cultural qualities, injury prevention, unstable surface training, skill acquisition, and recovery strategies for the effective implementation of strength and conditioning interventions for snowboarding athletes.